The "weak state" concept: theoretical roots and practical implementation - Marina Zelinska; Anna Chechel (Cхід, 2019)
In the modern world, almost simultaneously in the texts on national security strategies of the United States and the European Union the weak states are mentioned as the main threat to security for the whole world. The relevance of the study lies in the fact that weak states have long been the subject of research by Western scholars. It covers the search for solutions to problems in several areas, including the post-Soviet transfer, the issues of the African continent development and formation, the study of security issues in the Middle East, and so on. The article attempts to identify discrepancies in definitions and categorizations, as well as to analyze the preconditions and ways to overcome the position of “weak state”, in particular in the foreign economic and security sector. The main theoretical approaches to the definition of weak states in the foreign literature have been analyzed, but in domestic research this question is very rarely raised by scientists. The threats to international security of countries with a "weak state" status have been summarized. The study concludes the definition and assessment of the weak states status, namely, weak states in different regions of the world and in particular in Ukraine. Within the framework of this research, it has first been proposed to clarify the definitions of "weak" and "failed" states, as well as to determine the principles of the weak state existence along with the neighboring large country, and clearly defined preconditions and ways of overcoming its political and economic weakness, on the example of Ukraine.